Gravity-Induced Lower-Leg Swelling Can Be Ameliorated by Ingestion of α-Glucosyl Hesperidin Beverage - Nishimura, Naoki; Iwase, Satoshi; Takumi, Hiroko; Yamamoto, Keiko (Frontiers in Physiology, 2021)
The most likely cause of lower leg swelling is prolonged sitting, which sometimes induces deep vein thrombosis, also known as, economy class syndrome. We aimed to clarify the influence of intake of 4G-α-glucopyranosyl hesperidin (G-Hsp) beverage on the lower leg swelling caused by six hours of sitting in six healthy women. All subjects ingested 100mL of G-Hsp or Placebo beverages with 100mL of mineral water after ten minutes of rest in a chair. Subsequently, subjects were requested to sit in the chair in a relaxed position for six hours with two breaks to walk for urination. Calf water content measured by impedance plethysmography, calf circumference, calf skin temperature by infrared thermography, and toe skin blood flow by laser Doppler flowmetry were measured, along with assessment of calf swelling sensation on a visual analog scale. Increase in ankle % circumference was significantly less after the G-Hsp ingestion (101.8 ± 1.5%) than after placebo (103.3 ± 0.8%; P = 0.004). A significant difference was found between % circumference after the G-Hsp and the placebo, i.e., the calf swelling after placebo was significantly larger (P = 0.043). A gradual increase in skin temperature at the lower limb was observed after G-Hsp ingestion while there was no change after placebo. Gravity induced calf and ankle swelling resulted by prolonged sitting can be ameliorated by oral ingestion of hesperidin-derived G-Hsp through production of nitric oxide. It might be helpful in preventing economy-class syndrome caused by enforced sitting for a long duration.